Presentation for Anticipatory cash transfers for climate resilience: Evidence from experimental study in northeast Nigeria - Balana, Bedru; de Brauw, Alan; Adeyanju, Dolapo; Andam, Kwaw S.; Clingain, Clare; Olarewaju, Olukunbi; Yohanna, Ishiyaku (2023)
On December 4 to 7, 2023, The United Nations World Food Programme will host the first Impact Evaluation Forum in Rome, Italy.